Piggy hero : Handsome's heading for glory! - Jones, Pip (London Faber Limited, 2018)
Piggy Handsome is a very confident Guinea pig with a hugely inflated ego - he hails from a long line of very famous Guinea pigs. But sadly Handsome hasn't yet achieved world renown. After his last attempt Handsome realises that saving Jeff the budgie from falling off the roof would be just the thing to get on the front pages, but Jeff can't stop flapping his wings, because it's reflex. Piggy keeps pushing him off, Jeff keeps flying, much to Handsome's ire. Meanwhile the dastardly villains Dan and Dolly Dixon are seeking revenge for their time in prison. Can Handsome accidentally save the day once again?
3-5
Keywords: Language